Tomographic observations of gravity waves with the infrared limb imager GLORIA - Krisch, Isabell (2020)
Gravity waves drive global circulations in the mesosphere and stratosphere. Due to their small scales, they are usually not resolved in current global circulation models. Thus, their impact on the circulation is implemented in the form of simplified sub-models called parameterisation schemes. Several theoretical studies have highlighted that the assumptions on which these parameterisation schemes are based need to be reconsidered. However, the confirmation of these studies through measurements is still missing. A novel airborne remote sensing instrument, which can provide exactly such measurements, is the Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA). GLORIA has two different measurement modes suitable for gravity waves: full angle tomography and limited angle tomography. Full angle tomography allows for the reconstruction of the atmospheric temperature structure with a spatial resolution of 20 km in both horizontal directions and 200 m in the vertical at an accuracy of 0.5 K. This spatial resolution is very high for remote sensing instruments. Three-dimensional volumes reconstructed with limited angle tomography have a resolution of 30 km in flight direction, 70 km across flight track, and 400 m in the vertical at an accuracy of 0.7 K. Full angle tomography is better suitable for small-scale gravity waves with unknown orientation and limited angle tomography for non-stationary waves. The first gravity wave field investigated in this thesis was measured above Iceland on 25 January 2016. Driven by the full wave characterisation achieved from the GLORIA measurements, the Gravity wave Regional Or Global RAy Tracer (GROGRAT) reveals a strong oblique propagation of this wave covering more than 2000 km horizontal distance. This strong oblique propagation happens mainly in a narrow altitude band between 15 km and 20 km. Even though many studies predicted oblique gravity wave propagation, it still surprises that it take place in such a narrow altitude band. Further, GROGRAT shows that in the case of solely vertical propagation, which is a common assumption used for gravity wave parameterisation schemes, the wave momentum is deposited not only at a completely wrong geographical location but also at a wrong altitude. The importance of non-linear processes for gravity wave propagation is investigated on a second case study using GLORIA measurements taken above southern Scandinavia on 28 January 2016. The results of the linear propagation model GROGRAT with satellite measurements from the Atmospheric Infrared Sounder (AIRS) agree very well if a detailed observational filter is considered for the satellite measurements. Thus, non-linear processes seem to be negligible for the propagation of the investigated gravity waves. A further result of this study is, that one needs to consider the detailed observational filter of a measurement technique to draw meaningful conclusions from comparisons between observations and models. Schwerewellen treiben globale Zirkulationen in der Strato- und Mesosphäre an. Aufgrund ihrer kleinen Skalen werden Schwerewellen in der Regel in heutigen globalen Zirkulationsmodellen nicht aufgelöst. Daher wird ihr Einfluss auf die Zirkulation durch sehr vereinfachte Teilmodelle, genannt Schwerewellenparameterisierungen, angenähert. Mehrere theoretische Studien haben gezeigt, dass die diesen zugrunde liegenden Annahmen, dringend überdacht werden müssen. Allerdings fehlt diesen Studien bis heute die Bestätigung durch Messungen. Der flugzeuggetragene Infrarot-Horizontsondierer GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) kann eben solche Messungen bereitstellen. GLORIA hat zwei für Schwerewellen geeignete Messmodi: Vollwinkeltomographie und Teilwinkeltomographie. Diese Arbeit zeigt, dass beide Methoden geeignet sind mesoskalige Schwerewellen vollständig zu charakterisieren. Durch Vollwinkeltomographie lassen sich für die Fernerkundung sehr hohe räumliche Auflösungen von 20 km in beiden horizontalen Richtungen und 200 m in der Vertikalen bei einer Messgenauigkeit von 0.5 K erreichen. Mit Teilwinkeltomographie rekonstruierte Temperaturstrukturen haben horizontale Auflösungen in Flugrichtung von 30 km und quer zur Flugrichtung von 70 km. Die vertikale Auflösung liegt bei 400 m, die Messgenauigkeit bei 0.7 K. Vollwinkeltomographie eignet sich besser für kleinskalige Schwerewellen mit unbekannter Orientierung und Teilwinkeltomographie für zeitlich veränderliche Wellen. Das erste im Rahmen dieser Arbeit untersuchte Schwerewellenfeld wurde am 25. Januar 2016 über Island gemessen. Angetrieben durch die vollständige Wellencharakterisierung von GLORIA, zeigt das Schwerewellenausbreitungsmodell GROGRAT (Gravity wave Regional Or Global Ray Tracer) eine sehr stark horizontale Ausbreitung der Welle über eine Distanz von mehr als 2000 km. Diese stark horizontale Ausbreitung findet hauptsächlich in einem sehr schmalen Höhenband zwischen 15 km und 20 km statt. Obwohl mehrere Studien horizontale Ausbreitung von Schwerewellen vorhergesagt haben, ist die Ausbreitung in einem so schmalen Höhenband überraschend. GROGRAT zeigt auch, dass im Falle einer rein vertikalen Ausbreitung dieser Schwerewelle, wie sie in Schwerewellenparameterisierungen angenommen wird, der Schwerewellenimpuls nicht nur an der komplett falschen geographischen Position sondern auch auf der falschen Höhe abgelagert würde. Die Bedeutung von nicht-linearen Prozessen bei der Ausbreitung von Schwerewellen wird an einer zweiten Fallstudie mit GLORIA Messungen vom 28. Januar 2016 über Südskandinavien näher betrachtet. Vergleiche zwischen Ergebnissen des linearen Ausbreitungsmodells GROGRAT mit Satellitenmessungen des Atmospheric Infrared Sounder (AIRS), zeigen, unter Einbeziehung des vollständigen Beobachtungsfilters des Satelliteninstruments, eine gute Übereinstimmung. Dies lässt darauf schließen, dass nicht-lineare Prozesse bei der Ausbreitung dieser Schwerewelle keine Rolle gespielt haben. Als Nebenergebnis zeigt diese Studie auch, dass die Anwendung des vollständigen Beobachtungsfilters zwingend erforderlich ist, um sinnvolle Schlüsse aus dem Vergleich zwischen Messung und Modell ziehen zu können.